Analisis Praktik Ojek Wisata Ditinjau dari Transaksi Ekonomi Islam (Studi Kasus Paguyuban Ojek Menara Kudus) (Institut Agama Islam Negeri Kudus, 2025)
AbstractThe practice of tourist motorcycle taxis plays a vital role in supporting tourist accessibility, especially in religious destinations such as the Menara Kudus. This research analyzes the application of Islamic economic values in the practice of tourist motorcycle taxis managed by the Paguyuban Ojek Menara Kudus, with a focus on justice, transparency, and the prohibition of gharar. This study uses a qualitative approach and case study method. This research collects data through in-depth interviews, observations, and document analysis. Using a purposive sampling technique, a sample consisting of motorcycle taxi drivers, association managers, and related parties who have insight into the application of Islamic economic values in the practice of tourist motorcycle taxis was obtained. The research results show that Islamic economic principles have been applied through the ijarah contract for determining tariffs, the syirkah contract in collective financial management, and the wakalah is implemented contextually, with adaptations to the local and social needs of the Kudus community. Transparency is reflected in the daily contribution mechanism and fair tariff agreements, while the socio-economic impact includes increasing workers' income, creating jobs, and strengthening the local economy. However, challenges such as the lack of education of members about sharia principles and the need for technology for further transparency need to be addressed. This study contributes to the development of Islamic economics literature in the tourism sector.Keywords: Practice of Tourist Motorcycle; Ijarah; Syirkah; Wakalah; Paguyuban Ojek Menara Kudus. AbstrakPraktik ojek wisata berperan penting dalam mendukung aksesibilitas wisatawan, terutama di destinasi religi seperti Menara Kudus. Penelitian ini menganalisis penerapan nilai ekonomi Islam dalam praktik ojek wisata yang dikelola oleh Paguyuban Ojek Menara Kudus, dengan fokus pada keadilan, transparansi, dan larangan gharar. Penelitian ini berpendekatan kualitatif dan metode studi kasus. Pengumpulan data melalui wawancara mendalam, observasi, dan analisis dokumen. Dengan teknik purposive sampling, diperoleh sampel yang terdiri dari pengemudi ojek, pengelola paguyuban, serta pihak terkait yang memiliki wawasan tentang penerapan nilai-nilai ekonomi Islam dalam praktik ojek wisata. Hasil penelitian menunjukkan bahwa prinsip ekonomi Islam telah diterapkan melalui akad ijarah untuk penetapan tarif, akad syirkah dalam pengelolaan keuangan kolektif, serta wakalah diimplementasikan secara kontekstual, dengan adaptasi terhadap kebutuhan lokal dan sosial masyarakat Kudus. Transparansi tercermin dalam mekanisme iuran harian dan kesepakatan tarif yang adil. Dampak sosial-ekonomi meliputi peningkatan pendapatan pekerja, penciptaan lapangan kerja, dan penguatan ekonomi lokal. Namun, tantangan seperti kurangnya edukasi kepada anggota tentang prinsip syariah dan kebutuhan teknologi untuk transparansi lebih lanjut perlu ditangani. Penelitian ini berkontribusi pada pengembangan literatur ekonomi Islam di sektor pariwisata.Kata Kunci: Praktik Ojek Wisata; Ijarah; Syirkah; Wakalah; Paguyuban Ojek Menara.